Net Interest Margin and Capital Adequacy ratio: Mediating influence of Bank Profitability - Wahyudin, Agus; Kiswanto, Kiswanto; Nuhaaya, Ailin (Jurnal Dinamika Akuntansi, 2021)
Purpose: The objectives of this study are to analyze liquidity, credit risk, and operating efficiency on bank profitability as proxied by Return on Assets and analyze the role of Net Interest Margin (NIM) and Capital Adequacy Ratio (CAR) as an intervening variable.Methodology: The population in this study was banking companies listed on the Indonesia Stock Exchange (IDX) forÂ  2015-2019â€Ž. The sampling technique used the purposive sampling technique with 37 companies and 167 analysis units. The data analysis in this study used multiple linear regression analysis and path analysis using IBM SPSS Statistics 25 software as an analysis tool.Findings: The results show that liquidity and operating efficiency have a significant effect on profitability. Credit risk has a significant negative impact on profitability. On the other hand, NIM and CAR have a significant positive impact on profitability. Liquidity has a significant positive effect on NIM and CAR, credit risk has an insignificant negative impact on NIM but a significant positive on CAR, and operational efficiency has a significant negative impact on NIM. Meanwhile, NIM and CAR can only mediate liquidity to profitability. Otherwise, CAR can be mediating credit risk to profitability.Originality: NIM and CAR can be mediate the effect of liquidity on profitability, and in particular, CAR mediates market risk on profitability. Therefore, investors should pay attention to financial banking ratios to not fail in making investments.